More flexible and more innovative: the impact of flexible work arrangements on the innovation behavior of knowledge employees - Jiang, Liqun; Pan, Zhiyuan; Luo, Yunshi; Guo, Ziyan; Kou, Deqiang (Frontiers in Psychology, 2023)
Flexible work arrangements (FWA) are becoming increasingly widespread as an efficient means of coping with a dynamic and competitive business environment. Existing studies have primarily examined the impact of FWA as a management system; however, its impact on employee innovation behavior has not been fully explored. Based on the self-determination theory, this study constructed a moderated mediation model that empirically examined the influence of FWA on the innovation behavior of knowledge employees. Our findings are as follows: (1) FWA can activate innovation behavior among knowledge employees; (2) thriving at work plays a partial mediating role; (3) human resource policies that facilitate opportunities have a positive moderating effect. The findings fill a theoretical research gap and provide insights for managers on implementing FWA to promote the innovative behavior of knowledge employees.